Ectopic wisdom tooth at the mandibular ascending ramus: Case report and review of the literature. (1st April 2014) - Kansy, K.; Gander, E.; Staff, C.; Hoffmann, J.; Freier, K.
Abstract: Twenty to thirty per cent of wisdom teeth are partially or completely retained. A displacement of such teeth into the ascending ramus of the mandible is far less frequent with few reported cases in the literature. The case of a young lady and a review of the literature are presented. A 27‐year‐old woman was referred to the specialist department by her dentist. At the age of 22, a panoramic radiograph had been taken for an agenesis of the patient's lower left second molar. At this time, the lower left third molar was situated slightly submucosally at the angle of the mandible. In the present radiograph, the tooth had migrated into the ascending ramus of the mandible. Clinically, there was no pain, sensation disorder, disturbed occlusion, limited mouth opening or any other complaint. Due to significant tooth migration within the last 6 years, operative removal of the displaced tooth was recommended. Computed tomography showed that the distal root was in direct relation with the inferior alveolar nerve. Treatment was performed via a transoral approach. Post‐operative follow‐up was uneventful. This case stresses the importance of long‐time follow‐up of retained teeth and their immense potential for migration.